Evropski jeziki - Ožbot, Martina (Ars et humanitas, 2008)
The authors attempt to give an overview of some general external properties of the European languages today, defining the language families and languages which qualify for inclusion in this group and specifying the following features as characteristic of the European linguistic situation: relative stability since the early Middle Ages, given that there has been no considerable influx of new languages which would have radically altered the typological language map; a relatively low degree of typological heterogeneity; a relatively high degree of documentation; expansion of various "European languages" to other continents. With regard to the term "European languages", their Europeanness is problematized since, from a historical perspective, these languages are only partially justified to be considered as such. It is also proposed that the concept of "European languages" should be kept distinct from the related concept of "languages used/spoken in Europe". urther, the role of Latin as the single most important European language over the centuries and as a unifying feature of European culture is discussed. Parallels are drawn between Latin as the historical European lingua franca on the one hand and English as the modern language of international communication on the other: the importance of both languages started growing after substantial territorial expansion of their speakers and it was especially the political and economic power associated to these languages that played a significant role in their diffusion and long-term influence. Taking into consideration the instrumental as well as the symbolic function of languages, the question about the relationship between English and other European languages in today's Europe is dealt with; it is suggested that the European languages are in principle not endangered because of the spread of English, with the exception of those instances in which English has been taking over the functions they have traditionally performed as national languages. It is emphasized that the future of Europe is in the promotion of bi- and multilingualism, which have, in actual fact, been present on this continent throughout its history, and which in the cases of some European languages (e.g. Catalan, Basque, Irish, etc.) have been successfully enhanced over the past decades.
Keywords: evropski jeziki; Latin; latinščina; angleščina; English; lingua franca; nacionalni jeziki; ogroženost jezika; jezikovno načrtovanje